2005
DOI: 10.1158/0008-5472.can-04-2637
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of Tumors from a Human Colon Cancer Cell Line and from Ovarian Cancer Metastases in Immunodeficient Mice by a Single-Chain Ep-CAM-/CD3-Bispecific Antibody Construct

Abstract: Bispecific T-cell engager (BiTE) are a class of bispecific singlechain antibodies that can very effectively redirect cytotoxic T

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(75 citation statements)
references
References 19 publications
3
71
1
Order By: Relevance
“…At doses ≥48 µg/day, solitomab concentrations were comparable to published in vitro EC 90 values from colorectal cancer cell lines. 17 …”
Section: Resultsmentioning
confidence: 99%
“…At doses ≥48 µg/day, solitomab concentrations were comparable to published in vitro EC 90 values from colorectal cancer cell lines. 17 …”
Section: Resultsmentioning
confidence: 99%
“…Epithelial cell adhesion molecule was also selected as target for bi-and trispecific antibody therapies. Three T-cell activating, single-chain bispecific antibodies were shown to potently eradicate established and disseminated tumours in immunodeficient and -competent mouse models (Peters et al, 2004;Brischwein et al, 2005;Schlereth et al, 2005a, b), and a related bispecific antibody called E3Bi demonstrated high in-vitro cytotoxicity (Ren-Heidenreich et al, 2004). The trifunctional antibody catumaxomab (anti-Ep-CAM Â anti-CD3) has been safely administered in a phase I/II study to patients suffering from malignant ascites (Stroehlein et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…First, BiTEs bear a relatively short half-life, which will require appropriate dosing schedule (Lewis et al, 2002;Schlereth et al, 2005). Second, the impact of immune evasion mechanisms of tumor cells on BiTEs efficacy needs to be analysed.…”
Section: Bispecific Antibodiesmentioning
confidence: 99%